Can religious institutions promote sustainable behavior? Field experimental evidence on donations towards a carbon-offsetting fund - Christoph Feldhaus; Marvin Gleue; Andreas Löschel (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2019)
We conduct a field experiment with the visitors of the German Catholic Convention in Münster, Germany. We aim at investigating the effect of the announced attitude of a Catholic institution concerning climate protection efforts, of people's experimentally induced religiosity (using a priming intervention) and of the corresponding interaction on people's willingness to donate to a carbon-offsetting fund. Our results suggest that the supporting signal by the Catholic institution substantially increases donations by about 56 %. We observe neither a direct effect of the induced religiosity nor an interaction with the institution's signal. Our results thus indicate that religious authorities can promote sustainable behavior. As we observe no evidence that the signalmainly influences particularly religious people, we further conclude that religious institutions may serve as more general authorities when it comes to sustainable behavior rather than solely as leaders of those aiming to follow religious prescripts.
Keywords: C93; D64; D91; Q56; Z12; 330; Sustainable behavior; Field experiment; Religiosity; Priming; Carbon offsets